Development and displacement risks - Boyer, G; McKinnon, M (Refugee Studies Centre, University of Oxford, 2015)
Climate change has such significant implications for emergencies that sometimes the development facet of the challenge can be overlooked. Yet the impact of climate change induces systemic patterns of socio-economic erosion that also affect the dynamics of disaster displacement and that require parallel responses.